2021
DOI: 10.21203/rs.3.rs-107427/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized, Controlled Study on the Safety and Efficacy of Maraviroc and/or Favipiravir vs Currently Used Therapy in Severe COVID-19 Adults. “COMVIVIR” Trial.

Abstract: Multiple studies have established that hyperinflammatory response induced by SARS CoV-2 is a main cause of complications and death in infected subjects. Such dysfunctional immune response has been described as a dysregulated and exacerbated production of cytokines and chemokines that attracts and activates inflammatory cells, which start and sustain pulmonary and systemic damage, thus causing complications that lead to multi organ failure and death. Therefore, we suggest that blocking key inflammation receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…According to the available data, it has been observed that the median incubation period of individuals who were exposed to a single case of Nipah virus is approximately nine days, with a range of 6 to 11 days [9]. However, it is important to note that the time interval between exposure and the onset of illness can vary between 6 to 16 days, as reported in previous studies [10,11,12,4]. According to research conducted in Bangladesh, it has been determined that the median incubation period from the time of consuming raw date palm sap to the onset of illness is 7 days.…”
Section: Incubationmentioning
confidence: 90%
See 1 more Smart Citation
“…According to the available data, it has been observed that the median incubation period of individuals who were exposed to a single case of Nipah virus is approximately nine days, with a range of 6 to 11 days [9]. However, it is important to note that the time interval between exposure and the onset of illness can vary between 6 to 16 days, as reported in previous studies [10,11,12,4]. According to research conducted in Bangladesh, it has been determined that the median incubation period from the time of consuming raw date palm sap to the onset of illness is 7 days.…”
Section: Incubationmentioning
confidence: 90%
“…Favipiravir: is a ribonucleotide analog, is known for its ability to specifically target the viral RNA polymerase enzyme. By doing so, it effectively inhibits the replication and transcription processes of RNA viruses, resulting in broad-spectrum antiviral effects [11]. According to a study conducted by Dawes BE et al, it was demonstrated that the drug, when administered orally in in vivo simulation models using hamsters, at a dosage of 300 mg/kg/day twice daily, did not lead to any observed morbidity and resulted in a 100% survival rate [18].…”
Section: Anti-viral Therapymentioning
confidence: 99%